2007
DOI: 10.1001/archotol.133.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Differential Diagnosis of Chronic Dizziness

Abstract: To improve treatment outcomes for patients with chronic dizziness by identifying clinical conditions associated with persistent symptoms and delineating key diagnostic features that differentiate its causes and direct attention to specific treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
2
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(158 citation statements)
references
References 16 publications
6
136
2
7
Order By: Relevance
“…Therefore, dizziness in elderly is not necessarily associated with vestibular disease. Special attention should be paid to proprioceptive alterations, which are mentioned as being the primary cause for imbalance in 7% of the aged population (10,22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dizziness in elderly is not necessarily associated with vestibular disease. Special attention should be paid to proprioceptive alterations, which are mentioned as being the primary cause for imbalance in 7% of the aged population (10,22).…”
Section: Discussionmentioning
confidence: 99%
“…This clinical diagnosis was similar in many ways to PPV, but focused primarily on physical not psychological symptoms. Table 1 Features of PPV, SMD, VV, and CSD that informed the definition of PPPD PPV [13] SMD [39] VV [15] CSD [79,81] Primary Symptoms (criteria A. [76] Included in the definition of CSD were persistent nonvertiginous dizziness or unsteadiness, heightened sensitivity to motion of self or objects in the environment, and difficulty performing tasks that required precise visual focus.…”
Section: Contemporary Contextmentioning
confidence: 99%
“…The earliest reports of VV [15] also focused on situational symptoms, though recent investigations identified a link between persistent VV and chronic dizziness [22,23]. Definitions of CSD [75,79] emphasized chronic symptoms lasting throughout the day and exacerbated by motion stimuli. One study found that symptoms of CSD were absent or mildest for about an hour after patients awoke in the morning, but then increased as the day progressed [27].…”
Section: Temporal Pattern Of Symptomsmentioning
confidence: 99%
See 2 more Smart Citations